SAVIT Tabletop Game: A Serious Game to Support the Integration of Spontaneous Volunteers in Disaster Risk Management - Branlat, Matthieu; Floch, Jacqueline (Proceedings of the International ISCRAM Conference, 2026)
Despite the wide range of solutions available for integrating spontaneous volunteers into Disaster Risk Management (DRM), formal actors often remain hesitant to involve spontaneous volunteers and frequently lack the capacity to plan for and coordinate their engagement effectively. This paper presents our experience in designing and evaluating a serious board game intended to support DRM actors in exploring existing solutions and reflecting on how these can be adapted to their specific contexts. Following a design science approach, the game was iteratively developed and refined, then evaluated in three collaborative workshops involving a diverse set of stakeholders. Data were collected through observation and structured debriefings. The workshops demonstrated that the game helps participants identify concrete, actionable solutions for potential implementation. Moreover, the gameplay fosters greater awareness of other actors’ perspectives and needs, thus strengthening collaboration across organisational boundaries. The design and development of the serious game reflect the fact that such artefact serves multiple purposes: conceptual, pragmatic and epistemic.